2008
DOI: 10.1021/jp804566k
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission Properties of Hybrid Carbon Nanotube−ZnO Nanoparticles

Abstract: ZnO nanoparticles are uniformly coated on the walls of carbon nanotubes (CNTs) via a straightforward process, and the particle size and interparticle distance can be controlled by coating time. The appropriate amount of coated nanoparticles effectively reduces the formation of various structural defects induced by oxygen or hydrogen atoms on the walls of CNTs, which can be evaluated through a decrease in the intensity ratio of disorder graphitic band (D peak) over graphitic C-C stretching band (G peak) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Furthermore, the local field strength predominates, and the emission current on top of the nanoparticles becomes stronger than that on the single MoS 2 petal, making it easier to emit to the vacuum. 28 Based on this theory, the vast distribution of nanoparticles can be considered as an effective coupling method in field emission material synthesis.…”
Section: Field Emission Studymentioning
confidence: 99%
“…Furthermore, the local field strength predominates, and the emission current on top of the nanoparticles becomes stronger than that on the single MoS 2 petal, making it easier to emit to the vacuum. 28 Based on this theory, the vast distribution of nanoparticles can be considered as an effective coupling method in field emission material synthesis.…”
Section: Field Emission Studymentioning
confidence: 99%
“…Synthesis of nanoscale inorganic crystals with controlled size, shape, and dimension has attracted intensive research interest, since they are potential building blocks for advanced materials and optoelectronic devices [1]. The fabrication of semiconducting metal sulfide nanostructures has been paid much attention in the past decades because of their unusual optical and electric properties and potential applications in nanodevices [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The higher β values for the composite samples when compared to pure CNTs are attributed to the presence of spherical SnO 2 nanoparticles which act as additional independent emission centers other than the CNT tips. Ho et al recently reported similar observations on ZnO/CNT hybrids with different ZnO layer density [29]. The SnO 2 /CNT composite from the microwave assisted wet impregnation method shows significantly enhanced FE when compared to its counterpart from conventional method which may be due to the increased number of SnO 2 nanoparticles that contributes to the local field strengthening and emission current.…”
Section: Resultsmentioning
confidence: 63%